How Digital Banking Mediates the Impact of Financial Decisions on ASEAN-5 Bank Performance - Rachmawati, Rani (Journal of Development Research, 2026)
This study investigates the mediating role of digital banking services in the relationship between traditional financial decisions and bank financial performance. Using an unbalanced panel dataset of 152 commercial banks across ASEAN-5 countries (Indonesia, Malaysia, Thailand, Singapore, and the Philippines) from 2013 to 2023, yielding 1,567 bank-year observations, we employ a robust mediation analysis framework grounded in Financial Intermediation Theory, the Resource-Based View, and Dynamic Capabilities. The empirical strategy combines fixed effects panel regression to control for unobserved heterogeneity with a bootstrapping procedure (5,000 resamples) to test the significance of indirect effects. Results confirm that digital banking penetration partially and significantly mediates the impact of funding decisions (retail deposit ratio) and investment decisions (IT expenditure intensity) on Return on Assets (ROA), as well as the impact of the cost of funds on ROA. The mediation effect is context-dependent, being substantially stronger for larger banks and for banks operating in countries with more advanced digital infrastructure. These findings bridge a critical gap in the literature by modelling digital services not as a parallel performance driver, but as a fundamental transmission channel that reconfigures traditional value-creation pathways in banking. The study provides actionable insights for bank managers to integrate digital and financial strategies, for regulators to view digital infrastructure as a component of financial stability, and for investors to adopt integrated valuation models.